Legal Status of Government Employees with Employment Agreements in the State Civil Service System - Safrida (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the legal position of Government Employees with Work Agreements (PPPK) within the State Civil Apparatus (ASN) system, as well as to examine the rights and obligations of PPPK and their differences from Civil Servants (PNS). The research method used is a qualitative method with a normative juridical approach through a literature study of relevant laws and regulations. The results show that PPPK holds a legitimate legal position as part of ASN and has a strategic function in the administration of government. However, the contractual nature of PPPK's employment status has implications for job security, social security, and career development. In addition, there remain differences in treatment between PPPK and PNS that have the potential to create inequality within the civil service system. Therefore, more comprehensive strengthening of regulations and policies is needed to ensure legal certainty and to create a fair and professional ASN system.